The relation of bacteria to nitrification - Logan, George (My University, 1902)
Introduction: Very long ago—so far back that the time which has elapsed, even were it capable of being expressed in a definite number of years, would be quite incomprehensible by us—the globe on which we live and which we call the earth, was in a highly heated condition, the intensity of the heat being so great that the materials composing the rocks which we now see around us were in molten condition. In the course of ages much of the earth’s heat was radiated into space; and this went on till at length the earth became sufficiently cooled for some portion of it to assume a solid state. It was probably in this manner that the first hard rock masses made their appearance on the earth’s surface. As the cooling continued, the water vapor, or steam, which must have been present in the hot atmosphere, became condensed into a liquid; the water itself was then subjected to the cooling influence of radiation, and in course of time the earth’s surface became inhabited by low forms of life. The effect of the sun’s heat in those far distant ages would be, as it is now, to cause the water on the earth’s surface to rise in the form of vapor, and so to form clouds. These clouds floating about in the higher atmosphere, would become sufficiently cooled for their water-vapor to be condensed and fall in the form of rain-drops to the earth. And from the amount of water that surrounded the barren earth at that time the evaporation and the condensation must have been intense and thus we have first evidence of wearing away and disintegration of rock.
Citation: Logan, George. The relation of bacteria to nitrification. Senior thesis, Kansas State Agricultural College, 1902.
Morse Department of Special Collections
Keywords: Bacteria; Nitrification; Geology; Soil; Theses